Are we hardwired? : the role of genes in human behavior - Clark, William R., 1938-; Grunstein, Michael (Oxford : Oxford University Press, 2000)
What role do genes play in governing behaviour? This volume provides a general introduction to one of the most controversial topics in human biology.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Behavior genetics